MATHEMATICAL MODEL OF NICKEL-GRAPHENE COMPOSITE INKS FOR JETTING PROPERTIES IN INKJET PRINTING - Thakur, Neha; Parasuraman Swaminathan,; Hari Murthy, (Malaysian Journal of Science, 2024)
The droplet formation process in inkjet printing is studied numerically and verified through a simulation model. The droplet formation process decides the printing quality of the coating, and a mathematical model is developed to understand the complete process from droplet formation to detachment. The Navier-Stokes equation is used to mathematically derive the droplet radius (rnumerical). COMSOL multiphysics is used for simulation and the radius (rsimulation) is calculated from the droplet mass. The rnumerical and rsimulation are compared for inks containing nickel, graphene, and nickel-graphene composite ink it is observed that the composite ink radiuses have the lowest difference (rsimulation - rnumerical =0.085µm). A droplet is formed at 1.47mm from the nozzle inlet, for nickel-graphene ink, and after 1.5mm for other pristine inks. The results are verified through Z number, velocity profile, and droplet mass. The droplet formation observed from the velocity profile is earliest at 120µs. It is seen that a stable droplet is generated at 100µs for nickel-graphene ink and at 200 µs for individual inks.